Open-source Video Recording Scheduler - Abd. Hadi, Mohd Azhar (Universiti Teknologi Petronas, 2005)
This report explains about the project on developing a video recording scheduler application on open-source platform. The scope of this project is developing a GUI application that allows users to set the video recording schedule, and users are capable to set the codec used for recorded video compression. This application would run on open-source platform, therefore the target users is the open-source user that have a problem in using current open-source applications especially novice users. This project would be completed phase by phase, and for application development, the method applied is evolutionary development approach. This project depends on open-source tools and platform for application development. The end product of this project is able to perform all targeted features without producingany errors or machine problems. As a conclusion, this project has achieved its objectives in order to solve some problems of open-source users in scheduling theirvideo recording.